Konzept Deutsch als Fremdsprache nach Englisch (DaFnE) – Notwendigkeit oder Wunschvorstellung? Empirische Untersuchung in Grundschulen in Großpolen - Wypusz, Joanna (Glottodidactica, 2015)
DaFnE (German abbreviation: Deutsch als Fremdsprache nach Englisch – German after English) is an approach to teaching German as a third language to students who have already learned English. This methodology, which combines a first language (L1) with English as a second language (L2) and German as a third language (L3), is gaining popularity in Poland. This article contains both theoretical background and empirical research related to DaFnE. The first part introduces relevant definitions, aims of the DaFnE method and a short history of Tertiary Language Learning. The second part discusses teaching materials, which were created by the author of the article and used during empirical research in primary schools in the region of Greater Poland. Additionally, the paper includes results of surveys among the students and interviews among the German teachers.